Euphemisms in Olaf Scholz’s Speech on the Palestinian Tragedy - Suzana Alvertina Arsieardani; Agus Ridwan (Universitas Nusantara PGRI Kediri, 2026)
The humanitarian tragedy unfolding in Palestine has sparked a wide range of diplomatic reactions from world leaders, including German Chancellor Olaf Scholz. Communicating information related to this sensitive issue requires careful word choice, which is closely linked to the use of euphemisms as a linguistic strategy. This study was conducted to identify the forms of euphemism and their functions present in Olaf Scholz’s speech regarding the Palestinian tragedy. This is a qualitative descriptive study, with data consisting of the text of Olaf Scholz’s speech on the Bundesregierung website. Data analysis in this study employs Schröder’s theory of euphemism. The results of this study indicate that Olaf Scholz’s speech contains forms of euphemism, including metaphors, ambiguous expressions (vague or ambiguous phrases), omissions (omissions/zero euphemisms), generalizations, litotes, and stylistic incongruence. Furthermore, these forms of euphemism serve to obscure (verschleiernd) and conceal (verhüllend). However, in Olaf Scholz’s speech, the dominant function is the obscuring function (verschleiernd). This function is employed as a form of consideration for the speaker in selecting neutral language.